Exploring the Alentejo continental shelf for minerals and Quaternary environmental changes: preliminary results of the MINEPLAT survey. - Noiva, João (2016)
This study presents the preliminary results of MINEPLAT survey, organized by Universidade de Évora in partnership with Instituto Português do Mar e da Atmosfera (IPMA) based on an integrated analysis of geophysical data namely, ultra-high resolution seismic data (UHRS), multibeam data, backscatter data and magnetic data. The survey took place on north Alentejo continental shelf (30 to 200 meters depth) between Tróia and Sines. The interpretation and integration of the acquired data allows substantial improvement on the knowledge on the morphology and geology of the surface and subsurface of the Alentejo continental shelf towards the assessment of the mineral resources potential in the continental shelf off Alentejo and of the environmental conditions caused by the tectonic uplift in the Pliocene-Quaternary.